Quantum dot light emitting diodes for multiplex gas sensing - Yu Weiyong (2017)
A gas detection device comprising a light emitting source including a first plurality of quantum dots of substantially discrete size and made of a semiconductor material a gas cell to contain the gas to be detected and a light detector.